Developing a system to utilize a surveillance data for evidence-based public health interventions: Sleman HDSS’s experience - Fatwa Sari Tetra Dewi; Septi Kurnia Lestari; Ibtidau Niamilah; Hanifah Wulandari (Journal of Community Empowerment for Health, 2020)
Health interventions aim to improve health status in a community. Factors that influence the effectiveness and success of intervention programs include the characteristics of problems and the target population. Sleman Health and Demographic Surveillance System (HDSS) collects data on demographics and public health status annually. By 2018, we have conducted four cycles of data collection from 5,147 households. Results from Sleman HDSS could provide important information regarding the characteristics of target populations and health-related problems they face. The present paper describes how we develop a system that uses the data from a surveillance system to inform the development of health intervention programs. Aside from collecting survey data, Sleman HDSS field staff also recorded statements from respondents and community leader regarding health issues which they thought needed to be addressed. We used both quantitative and qualitative information to identify problems and locations that should be the priority. This priority list then distributed to the academic communities in the Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, (FMPHN-UGM) Yogyakarta, Indonesia. By 2018, we have completed 20 health educations and 10 community empowerment activities in collaboration with academic communities of the FMPHN-UGM. We concluded that health surveillance activities could support the development of effective evidence-based health intervention programs.